Relationship Between Library Instruction Programme and the Academic Performance of Law Students in Obafemi Awolowo University, Ile-Ife, Nigeria - Adegboye, O.A. (Ghana Library Journal, 2006)
This work examined the significance of evaluating the Library Instruction Programme (LIP) with a view to drawing a relationship between the LIP and the academic performance of students using the law students of the Obafemi Awolowo University, Ile-ife in southwestern Nigeria as a case study. The study adopted the survey design method and a total enumerate study of 342 part 5 final year law students in the 2002/2003 academic session who were expected to have been exposed to the LIP in their first year of study in the university was carried out. Using the questionnaire method, a total of 318(92.98%) retrieved questionnaire were analysed using descriptive and inferential statistics at the significant alpha level of 0.05. Findings revealed that the independent variables namely; sex age, marital status, qualification (of respondents); knowledge of LIP and content of LIP were jointly positively correlated with the students' academic performance at R = 0.880. Also, the composite effect of the independent variables revealed a significant positive relationship at P